Stamp with portrait of Hans Egede, 1686-1758, Danish-Norwegian priest and missionary, known as ... : Dansk frimærke med portræt af Hans Egede, 1686-1758, dansk-norsk præst og missionær, kendt som Grønlands apostel - Unknown (University of Southern California Digital Library (USC.DL), 2015)
Stamp with portrait of Hans Egede, 1686-1758, Danish-Norwegian priest and missionary, known as the Apostle of Greenland